Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Nguyễn Thị Kim Thúy - Bộ Công thương (2016)
Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Nguyễn Thị Kim Thúy (Số: 11715/BCT-KH) ngày 06/12/2016